Voltage Tracking of a Multi-Input Interleaved Buck-Boost DC-DC Converter Using Artificial Neural Network Control - Buswig, Yonis. M.; Othman, Al-Khalid; Julai, Norhuzaimin; Yi, Sim Sy; Utomo, Wahyu Mulyo; Lim Meng Siang, Alvin John (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper proposes an artificial neural network (ANN) voltage tracking of multi-input interleaved buck-boost DC-DC converter. A back-propagation algorithm topology is implemented in this paper. The control unit is implemented to ameliorate the performance of the proposed multi-input converter during transient dynamic response and steady-state operation mode. The neural network controller unit design, which is adaptive against output voltage command tracking and reference voltage variations is proposed. The proposed design has been verified through the MATLAB software. The simulation outcomes emphasized the validity and reliability of the proposed neural network technique, which would be a promising an efficient control method that ensures multi-input converter suitable for electric vehicle and renewable energy application systems.